As expressões nominais na construção da coesão referencial em textos de opinião produzidos por participantes do PAS II - Braga, Cláudia Alves Pereira (2022)
This paper addresses the issue of referential cohesion and aims to analyze the role of nominal expressions in the construction of referential cohesion in opinion texts of candidates of the Serial Evaluation Selective Process - PAS, at the Federal University of Lavras. Referential cohesion will be approached from a functionalist perspective, from the standpoint of language in use. For this study the following problem was formulated: what mechanisms are employed by PAS II candidates to establish referential cohesion through nominal expressions in opinion texts? In this sense, the general objective of this work is to analyze the use of nominal expressions in the construction of referential cohesion in opinion texts produced by candidates of the serial process - PAS of UFLA and, as specific objectives, are listed: (i) compile theoretical studies on referential cohesion; (ii) analyze the mechanisms used by these candidates to establish referential cohesion, through nominal expressions; (iii) analyze the use of nominal expressions as an argumentative strategy in the texts produced. The theoretical framework will be based on: Antunes (2005); Koch (2005); Marcuschi (2008) Martelotta, (2011), Neves (2011), Roncarati (2010), Cavalcante (2012) and others. For data generation, 100 texts were randomly selected, among the texts that constitute the set of PAS essays developed in 2019. The corpus was divided into three groups according to the range of scores of the essays in the sample, in a total of 20 points. The analysis privileged an exploratory approach that sought to interpret the cohesive phenomena/mechanisms with a focus on the referential cohesion process. The results of the analysis indicated that the Group I texts, which grouped the texts that received an average percentage ranging from 71 to 100% of the text production scores, used nominal expressions in order to perform cohesive functions. The use of encapsulating anaphora and hyper/hyponyms was also observed in order to contribute to textual progression and argumentation. In Group II, texts that received an average percentage between 41% and 70% of the marks for text production, the use of nominal expressions was observed in order to contribute to the argumentation and textual progression, as well as problems in the use of some expressions that impaired the text. In Group III, texts that received an average percentage of between 10% and 40% of the marks for the text production were grouped together; there was recurrent use of repetition of terms and expressions, which hinders the progression of the text; use of nominal expressions that are not from the same semantic field as the requested theme, and inadequate use of encapsulating anaphora.